THE LIBRARY MANAGEMENT ROBOT (International Journal of Engineering and Computer Science, 2014)
This paper demonstrates the application of Robot for library inventory management system. A robot is designed using sensor operated motors to keep track the library book shelf arrangements. Robot get the data of book which going to be search from the pc through Zigbee, The robot carries a barcode reader which collects the barcode data from the books arranged in a vertical manner and compares the decoded barcode data with the  input. If the particular book which is to be found out by the robot, then the robot gives location of the book to the librarian’s system through Zigbee, in which the robot is used for searching purpose. In case of any difficulty faced by the robot when it does the searching process, the robot halts and sends an alarm. Misplaced books can be identified using the pre-programmed data in the robot which helps to maintain the books in an order. This helps and simplifies the job of monitoring the arrangement of books and also reduces the manual routine work done by the library staff.